PIDA-induced oxidative C–N bond coupling of quinoxalinones and azoles - Watchara Wimonsong (2022)
A metal-free promoted direct oxidative C–N bond coupling of quinoxalinones and azoles for the rapid and effective synthesis of potent pharmaceutical important 3-(azol-1-yl)quinoxalin-2-one has been developed. Employing PIDA as the easily available mediator, the desired coupling products were isolated in moderate to excellent yields with a good substrate scope under operational simplicity and mild reaction conditions. Preliminary mechanistic studies suggested that a radical process is likely to be involved in the reaction.